Quality Assurance for Frozen Fish (Decapterus sp) Utilizing Fault Tree Analysis at PT XYZ (Fish Freezing Company) - Sumartini; Wening Ratrinia, Putri; Efri Hasibuan, Nirmala; Husna, Wardatul (TALENTA Publisher, 2023)
Fish product quality is crucial, and any flaws in frozen fish, such as unpleasant odor, breakage, dents, tears, or texture damage, can negatively impact its overall quality. These defects can lead to reduced customer satisfaction and adversely affect the company's brand reputation. To enhance product quality, the company must establish an efficient quality assurance system and closely monitor the handling of raw materials. The main objective of this practical work is to identify potential risks of damage and develop strategies to prevent such incidents from occurring. The Fault Tree Analysis method is utilized to systematically identify and analyze the root causes of existing errors and find appropriate solutions to address the problem. The FTA results reveal 18 basic event factors that can cause damage to fish, including worker negligence during raw goods placement, inadequate use of plastic protection, lack of rubber carpets in baskets, failure to adjust freezing temperature properly, insufficient inspections, non-compliance with Standard Operating Procedures, improper fish arrangement, excessively hard freezing temperature, employee laziness and carelessness, absence of basket mats, prolonged freezing step, unset temperature checks, mishandling of raw goods due to a rush to finish quickly, and irregular temperature checking schedules. The study aims to understand the step-by-step process of handling flying catfish, identify the factors contributing to fish damage, and analyze the potential damage scenarios.